The phosphate transporter PHT4;1 is a salicylic acid regulator likely controlled by the circadian clock protein CCA1 - Wang, Guoying; Zhang, Chong; Battle, Stephanie; Lu, Hua (Frontiers in Plant Science, 2014)
The small phenolic compound salicylic acid (SA) plays a critical role in plant defense against broad-spectrum of pathogens. The phosphate transporter gene PHT4;1 was previously shown to affect SA-mediated defense and its expression is regulated by the circadian clock. To further understand how PHT4;1 affects SA accumulation, here we analyzed the genetic interactions between the gain-of-function mutant pht4;1-1 and several known SA mutants, including sid2-1, ald1-1, eds5-3, and pad4-1. The genetic analysis was conducted in the acd6-1 background since the change of acd6-1 dwarfism can be used as a convenient readout for the change of defense levels caused by impairments in some SA genes. We found that compared with the corresponding double mutants, the triple mutants acd6-1pht4;1-1ald1-1, acd6-1pht4;1-1eds5-3, and acd6-1pht4;1-1pad4-1 accumulated reduced SA and lower PR1 expression, suggesting that PHT4;1 contributes to acd6-1-conferred defense phenotypes independently of these known SA regulators. Although some triple mutants had wild type-like levels of SA and PR1 transcripts, these plants were smaller than wt and display minor cell death, suggesting that additional regulatory pathways contribute to acd6-1-conferred dwarfism and cell death. Our data further showed that circadian expression of PHT4;1 was dependent on CCA1, a central oscillator component of Arabidopsis circadian clock. Recombinant CCA1 protein was demonstrated to bind to the PHT4;1 promoter in electrophoretic mobility shift assays, suggesting a direct transcriptional regulation of PHT4;1 by CCA1. Together these results indicate that PHT4;1 is an SA regulator acting independently of several known SA genes and they also implicate a role of the circadian clock mediated by CCA1 in regulating phosphate transport and/or plant innate immunity.